Cloud Computing and its role in the Information Technology - Alam, Tanweer (Pandawan Sejahtera Indonesia, 2020)
The concept of Cloud Computing has been distinguished as one of the major computing models in recent years. Cloud computing has become a great innovation that has important consequences not just for services on the internet but also for the entire Information technology (IT) market. Its emergence aims to optimize on-demand technology, hardware and information provisioning as a service, reaching the economy of scale in the distribution and operation of IT strategies. A great deal of cloud computing research has been concerned over some obstacles and challenges that rely upon behind the lure of cloud computing. Security has been always raised as one of the most critical issues of cloud computing where resolving such an issue would result in constant growth in the use and popularity of the cloud. Security requirements represent a major issue that has to be met in order of easing some of these obstacles. This article presents the role of cloud computing in the IT sectors.